Business in the Qur’an and Sunnah: its importance and guidelines - Samsudin, Sofiah (2011)
Islamic history has given us undeniable proof on the contributions of the Muslims for the welfare of the public, achieving honour and economic prosperity in this worldly life, while still being governed by the Qur’an and the Sunnah. Today, the situation has shifted, where the deviation of Muslims from Islamic teachings has caused their decline, among other things. Hence, the practical scene of Islamic business has inevitably changed. It is evident that business no longer has a great impact on the Muslims in their lives. Two extreme sides emerge. On one side, there are Muslims who conduct business blindly and greedily based on the Western ideology that separates worldly and religious matters. On the other side are Muslims who avoid being involved in business, considering it as an immoral act of chasing after worldly life. These two sides have resulted in the passive movement of Muslims in business, which is one of the direct factors for their decline in today’s global economy . Therefore, it is crucial for us to examine the importance of business and its guidelines in the light of the Qur’an and the Sunnah, in order to generate more successful Muslim businessmen and businesswomen. As a matter of fact, the Muslims' revival depends entirely on their return to the purity of Islam. It is also crucial to mention the correlation between two types of business as described in the Qur’an and the Sunnah, which are Duniawi and Ukhrawi, and why Allah mentioned them repeatedly in the Qur’an. In order to prove what is being suggested by Qur’an and Sunnah, this paper presents examples of businessmen and businesswomen among the Sahabah and the Tabi`in who did business according to the guidelines provided to them by the teachings of the Prophet p.b.u.h.